Confidence limits of expected monthly rainfall for some selected stations in Peninsular Malaysia - CRONG , HU HING; TICK, LIM JOO (MAUSAM, 1977)
Monthly total rainfall for 15 stations in Peninsular Malaysia were analysed. The original, rainfall data were normalised by Bartlett s square root transformation. Confidence limits of expected monthly rainfall were calculated from the transformed data and reconverted back to the original units. Possible applications of the confidence limits of expected monthly rainfall to agriculture are briefly discussed.